Knowledge Of Trimester I Pregnant Women About Emesis Gravidarum - Agus Wahyu (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Backgroud: There are various causes of nausea and vomiting, including hormonal changes in the body, psychology, and lifestyle. Poor diet before or in the early weeks of pregnancy, lack of sleep or rest and stress can exacerbate nausea and vomiting. Some things that can be done to reduce nausea even though they cannot be completely eliminated, are to consume a balanced diet, get enough movement and get enough rest.